Microstructural, mechanical, and corrosion properties of S355J2 structural steels joined by MIG welding - Çalıgülü, Ugur; Özorak, Cihan; Daniş, Afif (My University, 2024)
In this study, the microstructural, mechanical, and corrosion properties of S355J2 structural steels welded by metal inert gas (MIG) welding method were investigated. Single surface and double surface welded structures were formed by MIG welding method using 2 different amperage values (200A, and 260A). The microhardness, tensile strength, corrosion and microstructure properties of the welded specimens were investigated. The structural and mechanical effects of different current values used on the material were analysed. Microstructure investigations show that fine grained structures start to coarsen and grain boundaries start to decrease due to welding heat input in the HAZ region. The highest hardness value was measured in the welded joint at 260A value in single surface welding due to rapid cooling and rapid solidification. Increases in yield strength and tensile strength were determined with increasing welding current and in the double-sided welding procedure. In the potentiodynamic corrosion test carried out in HCl solution, it was determined that the double-sided welded joint at 260A welding amperage and the double-sided welded joint at 260A was the most resistant to corrosion among the samples subjected to corrosion tests.
Keywords: Microstructure; Corrosion; Mechanical Properties; MIG Welding; S355J2 Structural Steel